Armazenamento de cereais no Espírito Santo: períodos viáveis e retornos - Melges Walder, Vladimir; Moreira Leite, Carlos Antônio; Brandt, Sérgio Alberto; Ladeira, Heloisa Helena (Revista Ceres, 2025)
Agricultural production is characterized by instability resulting from biological climatic conditions and seasonal variations which create difficulty for agricultural management.